1986
DOI: 10.2337/diab.35.8.855
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Autoimmune Diabetes Mellitus with Splenocytes from Nonobese Diabetic (NOD) Mice

Abstract: The nonobese diabetic (NOD) mouse, a model of human type I diabetes, develops insulitis beginning at 4-6 wk of age. By 30 wk of age, 72% of females and 39% of males develop spontaneous diabetes, apparently because of an overwhelming autoimmune response to the insulin-producing beta-cells within the islets. To identify the immune mechanism responsible for destruction of beta-cells in the NOD mouse, we developed an adoptive transfer protocol that induces diabetes in NOD mice at an age when spontaneous diabetes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
140
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(149 citation statements)
references
References 0 publications
9
140
0
Order By: Relevance
“…Thus, a clear autoaggressive potential of CD4 + T cells was seen, in line with several studies on BB-DP rats and NOD mice [7][8][9][10][11][12]. The predominant role of CD4 + T cells has been previously demonstrated by selective transfer of CD4 + or CD8 + T cells in immunodeficient NOD strains, whereas CD8 + T cell subsets were not diabetogenic [7,16].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Thus, a clear autoaggressive potential of CD4 + T cells was seen, in line with several studies on BB-DP rats and NOD mice [7][8][9][10][11][12]. The predominant role of CD4 + T cells has been previously demonstrated by selective transfer of CD4 + or CD8 + T cells in immunodeficient NOD strains, whereas CD8 + T cell subsets were not diabetogenic [7,16].…”
Section: Discussionsupporting
confidence: 85%
“…The only difference between the LEW.1AR1-iddm rat and the background strain is a mutation on chromosome 1 within Iddm8 (RNO1q43-51) [4,5]. Adoptive transfer of T cells from diabetic LEW.1AR1-iddm rats to prediabetic LEW.1AR1-iddm rats significantly increased the incidence of diabetes [6] in agreement with studies on NOD mice and BB-DP rats [7][8][9][10][11][12]. The autoreactive potential can be transferred through immune cells from diabetic LEW.1AR1-iddm rats into athymic nude LEW.1AR1-Whn rnu animals, but not to the diabetes-resistant LEW.1AR1 background strain [6].…”
Section: Introductionsupporting
confidence: 80%
“…NOD mice spontaneously develop autoimmune diabetes with immunopathological features resembling those of human disease and can be used as an animal model to study the pathogenesis of T1D. Previous studies have demonstrated that transfer of NOD CD4 1 T cells to immunodeficient NOD/SCID mice can induce diabetes in those recipients, indicating that CD4 1 T cells play an important role in the pathogenesis of diabetes [3,4]. Th1 cells have been closely linked with diabetic pathogenesis because IFN-g and IL-12 are upregulated in the inflammatory lesions in the pancreas and administration of IL-12 promotes autoimmune diabetes in NOD mice [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…First, the CY-accelerated diabetes model was chosen to test whether peptide immunization could counteract the effect of CY, which is secondary to abrogation of suppressor T cell function [15,16]. Second, to investigate whether active cellular mechanisms were associated with suppression of diabetes, splenocytes from peptide-immunized animals were cotransferred together with diabetes into young NOD mice using splenocytes from diabetic NOD donors [17]. Finally, T cell proliferation to the immunizing peptide or a panel of other synthetic peptides was investigated.…”
Section: Introductionmentioning
confidence: 99%